Prevalencia de la infección por Helicobacter pylori en población pediátrica y su relación con esofagitis eosinofílica (2025)
A descriptive, retrospective, and cross-sectional study was conducted. Gastric andesophageal biopsies from pediatric patients aged 1 month to 15 years at the Hospital San Vicente Fundación were analyzed, processed at the Pathology Laboratory of the University ofAntioquia. A total of 576 endoscopy reports with biopsy sampling were selected. Demographic, clinical, anthropometric variables, as well as endoscopic and histopathological findings were documented. Immunohistochemistry was applied in cases of active gastritis without HP evidence on hematoxylin-eosin staining. Statistical analysis was descriptive. The prevalence of HP infection was 20.5%, and 6 patients had concomitant HP infection and EE. Regarding clinical characterization, the most frequent symptom in patients with HP was abdominal pain (51.7%), while for EE it was both abdominal pain and hyporexia (35.3% each). About 30.5% of patients with HP were diagnosed within the first year of symptoms. Some infected patients showed nutritional status alterations, particularly acute malnutrition. The most frequent endoscopic findings were follicular gastropathy in HP patients and non-erosive esophagitis in EE patients. Histologically, all patients with HP presented with chronic gastritis; in EE, 76.5% had concomitant chronic gastritis. Additionally, immunohistochemical study allowed for the detection of HP in patients initially negative by hematoxylin-eosin staining.